Asset booms and tax receipts: the case of Spain, 1995- 2006 - Martinez- Mongay, C. (European Economy. Economic papers, 2007)
At about 3¾% for more than 10 years in a row, Spain is enjoying the longest period of sustained growth above the euro area since the late sixties. This period is also characterised by a combination of persistently low real interest rates and a dynamic demography, which has been feeding unprecedented growth in asset markets. In parallel, total-tax receipts have grown by about 4¼ percentage points of GDP, thus recording an elasticity with respect to GDP of 1.2. This paper discusses and assesses the extent to which the increase in tax receipts can be associated to changes in the composition of GDP, which would fade out after the current expansion tapers off. Econometric analyses provide evidence that 50 to 75 percent of the increase in tax revenues, observed in Spain between 1995 and 2006, might be of a transitory nature and would disappear with the asset boom. On this basis, in a context of significant composition effects, using standard tax elasticities may lead to an overestimation of structural revenues and to an incorrect assessment of the fiscal stance. This may be relevant in EMU because the likelihood of occurrence of asset booms may be relatively high when the monetary-policy stance is far from consistent with the country's inflation. Furthermore, in the specific case of Spain, the size of transitory composition effects associated to the current asset boom highlights the interest for the policymakers of the country to carefully assess the implementation of unfunded tax cuts and/or expenditure increases, especially those more difficult to revert in bad times.